The journey toward the integration of sustainability in apparel and textiles education: a case study. - Armstrong, Cosette M. (Kansas State University, 2011)
The UN has challenged higher education to integrate sustainability across all disciplines, declaring 2005-2014 the Decade for Educational for Sustainable Development (DESD) (UNESCO, 2003). Education for sustainable development (ESD), a UNESCO initiative, advocates for reorienting education away from the industrial model of education, and has significant pedagogical implications for cultivating knowledge, skills, and values thought to support sustainable development (Rode & Michelsen, 2008; Sterling, 2004). Responsive action to this call has been sluggish (Everett, 2008; Rode & Michelsen, 2008). Concurrently, product development and design protocol is becoming more progressive in an effort to limit the impact of products on people and the planet, and there is an urgent need to evolve apparel and textile (AT) curriculum to better prepare undergraduates for this evolution. ESD may provide a way forward, but little is known about how it may succeed current educational practice or how such practice may impact learners in AT. The purpose of this study was to examine the learning and development experience of students enrolled in an apparel product development (APD) course that has been redeveloped according to the ESD framework. A qualitative case study was conducted during one semester to examine how students experienced the course. Data collection included student reflective writings, focus group interviews, and a researcher reflexive journal. Also, a survey was utilized to determine how students perceived their progress in the development of skills related to ESD. Both theory-driven and inductive coding procedures were used to identify themes across the qualitative data. A repeated measures ANOVA was used to analyze the quantitative survey data. Results of the study indicate that students yielded a positive, though challenging, learning and development experience in the course, and one that was considered exceptional in comparison to other courses in the same program. Among the learning and development outcomes experienced in the course considered most important, according to students, were sustainability literacy and the development of change agent skills. Further, the pedagogical perspectives of ESD which influenced the course redevelopment were perceived to be highly impactful. The study has identified pedagogical and curriculum design approaches which may be used to integrate sustainability more effectively into the AT curriculum and better foster the development of change agent skills.
Keywords: Sustainability education; Textiles and apparel education; Curriculum; Qualitative; Business Education (0688); Higher Education (0745); Pedagogy (0456)